2022
DOI: 10.3390/jcm11061571
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Rifaximin in Japanese Patients with Hepatic Encephalopathy: A Multicenter Retrospective Study

Abstract: Background: Rifaximin is commonly used for hepatic encephalopathy (HE). However, the effects of long-term treatment for Japanese people are limited. Therefore, this study aimed to investigate the effects and safety of long-term treatment with rifaximin on HE. Methods: A total of 215 patients with cirrhosis administered with rifaximin developed overt or covert HE, which was diagnosed by an attending physician for >12 months. Laboratory data were extracted at pretreatment and 3, 6, and 12 months after rifaxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, non‐response in terms of ammonia decrease in these studies could be because of small sample size or the big spread in measurement outcomes owing to the difficulties in measurement of the volatile ammonia metabolite. Importantly, even long‐term studies and studies where rifaximin was used as add‐on to lactulose showed blood ammonia reduction by rifaximin (from 60 μmol/L to 47 μmol/L after 12 months and −40 μmol/L as add‐on respectively) 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, non‐response in terms of ammonia decrease in these studies could be because of small sample size or the big spread in measurement outcomes owing to the difficulties in measurement of the volatile ammonia metabolite. Importantly, even long‐term studies and studies where rifaximin was used as add‐on to lactulose showed blood ammonia reduction by rifaximin (from 60 μmol/L to 47 μmol/L after 12 months and −40 μmol/L as add‐on respectively) 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question remains whether the effects of rifaximin on the microbiota composition and ammonia concentration are mediated by direct effects on the microbiome or direct effects on the intestinal epithelium (leading to increased barrier function) or both. The capacity of rifaximin to lower blood ammonia levels was confirmed in a meta‐analysis of 12 trials and long‐term real‐world data studies 15–17 . We therefore hypothesized that rifaximin, next to its effects as an intestinal antibiotic also directly impacts the small intestinal epithelial biotransformation machinery by stimulating nitrogen detoxification.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Rifaximin inhibits ammonia-producing bacteria in the gut (17)(18)(19), lowers blood ammonia, and prevents hepatic encephalopathy (20)(21)(22). It is widely used in Europe and the United States in the treatment of hepatic encephalopathy.…”
Section: Introductionmentioning
confidence: 99%